Impact of the Sensitivity to Empiric Antibiotics on Clinical Outcomes after Biliary Drainage for Acute Cholangitis - Satoshi Kawamura; Yuki Karasawa; Nobuo Toda; Yousuke Nakai; Chikako Shibata; Ken Kurokawa; Junya Arai; Kazuyoshi Funato; Shigeyuki Kurosaki; Shuya Maeshima; Mayuko Kondo; Kentaro Kojima; et al. (Gut and Liver, 2020)
Background/Aims: Empiric antibiotics are given in combination with biliary drainage for acute cholangitis but sometimes turn out to be insensitive to microorganisms in blood and bile. Clinical outcomes were compared according to sensitivity to microorganisms detected in blood and bile culture to evaluate the impact of sensitivity to empiric antibiotics in cholangitis. Methods: Consecutive patients who underwent biliary drainage for acute cholangitis were retrospectively studied. Clinical outcomes such as 30-day mortality, length of hospital stay and high care unit stay, organ dysfunction and duration of fever were compared in three groups: group A (sensitive to both blood and bile culture), group B (sensitive to blood culture alone) and group C (insensitive to both blood and bile culture). Results: Eighty episodes of cholangitis were classified according to sensitivity results: 42, 32 and six in groups A, B and C. Escherichia coli and Klebsiella were two major pathogens. There were no significant differences in 30-day mortality rate (7%, 0%, and 0%, p=0.244), length of hospital stay (28.5, 21.0, and 20.5 days, p=0.369), organ dysfunction rate (14%, 25%, and 17%, p=0.500), duration of fever (4.3, 3.2, and 3.5 days, p=0.921) and length of high care unit stay (1.4, 1.2, and 1.7 days, p=0.070) in groups A, B and C. Empiric antibiotics were changed in 11 episodes but clinical outcomes appeared to be non-inferior even in 31 episodes of cholangitis who were on inadequate antibiotics throughout the course. Conclusions: Sensitivity of empiric antibiotics was not associated with clinical outcomes in acute cholangitis.